Temporal and geographical variations of thyroid cancer incidence and mortality in France during 1986–2015: The impact of overdiagnosis. (December 2021) - Li, Mengmeng; Delafosse, Patricia; Meheus, Filip; Borson-Chazot, Françoise; Lifante, Jean-Christophe; Simon, Raphael; Groclaude, Pascale; Combes, Jean-Damien; Dal Maso, Luigino; Polazzi, Stéphanie; Duclos, Antoine; Colonna, Marc; et al.
Abstract: Background: France is among the countries showing fastest growth of thyroid cancer (TC) incidence and highest incidence rates in Europe. This study aimed to clarify the temporal and geographical variations of TC in France and to quantify the impact of overdiagnosis. Methods: We obtained TC incidence data in 1986–2015, and mortality data in 1976–2015, for eight French departments covering 8% of the national population, and calculated the age-standardised rates (ASR). We estimated the average annual percent changes (AAPC) of TC incidence, overall and by department and histological subtype. Numbers and proportions of TC cases attributable to overdiagnosis were estimated by department and period, based on the comparison between the shape of the age-specific curves with that observed prior to changes in diagnostic practice. Results: During 1986–2015, there were 13, 557 TC cases aged 15–84 years. Large variations of TC incidence were observed across departments, with the highest ASR and the fastest increase in Isère. Papillary subtype accounted for 82.8% of the cases, and presented an AAPC of 7.0% and 7.6% in women and men, respectively. Anaplastic TC incidence decreased annually 3.0% in women and 0.8% in men. Mortality rates declined consistently for all departments. The absolute number (and proportion) of TC cases attributable to overdiagnosis grew from 1074 (66%) in 1986–1995 to 3830 (72%) in 2006–2015 in women, and varied substantially across departments. Conclusions: Overdiagnosis plays an important role in the temporal and regional variations of TC incidence in France. Monitoring the time trends and regulating the regional healthcare practice are needed to reduce its impact. Highlights: Mortality rates of TC and incidence of anaplastic subtype declined in France. Spatiotemporal variability in TC incidence was mainly driven by overdiagnosis. Overdiagnosis varied among age groups, across regions, and over time.